Iowa RBA, November 10, 1997 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1997)
Email of the Iowa RBA update for November 10, 1997. Highlights of the update include numerous outstanding sightings, including a male Pine Grosbeak, an Evening Grosbeak, a first year Great Black-backed Gull, and a first year Thayer's Gull. Also of note were observations of White-winged Scoters, White-winged Crossbills, a Bohemian Waxwing, and a Spotted Towhee. Also included are handwritten notes for the next week's update with sightings of a Red-shouldered Hawk, a female Long-tailed Duck, and 8 adult Trumpeter Swans. Epson - sheet feed/flatbed